STUDI TENTANG BUDAYA SEKOLAH DAN KARAKTER DISIPLIN SISWA DI MTs PONPES BUSTANUL HUDA DESA KOTA GARO KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Refi Ermilis; Hambali '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The background of this research with their school culture such as teamwork, ability and skills, respectful, honest, and discipline. And the student discipline code like: going to school on time, ending the learning activities and return schedule has been determined, using the completeness school uniforms as regulations, maintain the neatness and cleanliness of clothing according to the rules of the school. Follow and implement extracurricular activities specified in the Sschool, through the whole process of learning well and active, when unable to attend to school then it must include a notice to school, working on the assignment of teachers, carrying out tasks in accordance picket picket predetermined schedule. With this student discipline code, students can apply the school and community environment. The problem of this research is Is there a study of the school culture from the perspective of teachers and students study on the character of discipline from the perspective of students in MTs Ponpes Bustanul Huda City Village Garo Tapung Hilir District of Kampar regency. The purpose of this study was to determine how the school culture from the perspective of teachers and to determine how the student discipline code according to the student's perspective. The research was done in MTs Ponpes Bustanul Huda City Village Garo Tapung Hilir District of Kampar regency. Samples of this research for a school culture sample as many as 30 teachers of teachers. As for the character of student discipline 30 students. Data collection techniques by using observations, questionnaires, literature and documentation. Data analysis techniques performed by descriptive quantitative, in processing the data obtained from a questionnaire distributed to respondents is presented in the form of a percentage, using the formula P = F / N x 100%. Based on the writer's observation that the field study of the culture of the school and the student discipline code in mts Ponpes Bustanul Huda City Village Garo Tapung Hilir Subdistrict Kampar regency was